(untitled) (NTU Journal of Agriculture and Veterinary Science, 2023)
Abstract. The results of a study of the effect of olive cultivars in Kowal, Nepali, Khastawi, and Syria, and tree orientation, on the seasonal activity of the olive leaf fly, Dasineura oleae, showed that the infection appeared at the end of February 2022 in the form of swellings on young and tender leaves. The highest average infection was on 28/2 and reached 8.78 swellings / 10 leaves, while the lowest average infection was 1.62 swellings / 10 leaves. The Bakwal verity was the most sensitive cultivar to infestation with the olive leaf fly, with an average infection rate of 8.08 swellings / 10 leaves, followed by the Nepali verity with 4.98 swellings / 10 leaves, and Al Khastawi with 3.98 swellings / 10 leaves .While the Syrian variety was the most resistant variety, with an average of 2.58 swellings / 10 leaves, and the results showed that the eastern side was the preferred side for the insect, with an average infestation of 8.15 swellings / 10 leaves, followed by the southern side, 5.00 swellings / 10 leaves, the northern side 3.88, and finally the western side, 2.58 swellings / 10 leaves. The results of the correlation values ??were positive and significant between temperature and insect infestation positive and significant correlation between temperature and insect infestation for Bakool, Nepali and Syrian verities, negative and significant with the Khastawi verity, and negative and significant between the relative humidity and the same verities and positive and significant with the Khastawi verity.